Prevalence of thyroid autoantibody positivity in women with infertility: a systematic review and meta-analysis - Yingqin Huang; Baoli Xie; Jiaxu Li; Fu Hang; Qianwen Hu; Yufu Jin; Rongyan Qin; Jiaxin Yu; Jianxin Luo; Ming Liao; Aiping Qin (BMC, 2024)
Abstract Background Thyroid autoimmunity (TAI) is associated with infertility and complications during pregnancy. However, the prevalence of thyroid autoantibodies in women with infertility remains unclear due to variability in study designs, sample sizes, and populations. In this meta-analysis, we aimed to assess the prevalence of thyroid autoantibodies in women with infertility compared with that in healthy controls. Methods Systematic searches were conducted across PubMed, Embase, Web of Science, and the Cochrane Library from inception to February 5, 2024. The inclusion criteria were women with infertility and those with autoimmune thyroid antibodies. Studies in which relevant data could not be extracted, randomized control trial reports, studies with non-original or duplicate data, and non-English articles were excluded. The main outcome was prevalence rate. Results The worldwide pooled prevalence of thyroid autoantibody positivity was 20%. In contrast, a significantly higher TAI prevalence was noted in the population with infertility than in healthy controls (risk ratio [RR] = 1.51). Subgroup analyses indicated that TAI prevalence was higher in patients receiving both assisted reproductive technology (ART) and non-ART treatments than in healthy controls (RR = 1.37 and 3.06, respectively). TAI prevalence was also higher in the recurrent abortion and non-recurrent abortion groups of infertility than in healthy controls (RR = 1.80 and 1.39, respectively). Additionally, a higher TAI prevalence was found in the euthyroid and non-simple euthyroid groups than in the control group (RR = 2.77 and 1.43, respectively). The prevalence was significantly higher in cases of unexplained infertility, endometriosis, ovulation disorders, and fallopian tube factors among women with infertility than among the control group (RR = 1.53, 1.83, 1.42, and 2.00, respectively). Conclusions Thyroid autoantibodies are more prevalent in patients with infertility than in healthy controls. Given the presence of thyroid autoantibodies, screening patients with infertility is clinically important.